2013
DOI: 10.1016/j.cellsig.2013.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Chibby drives β catenin cytoplasmic accumulation leading to activation of the unfolded protein response in BCR-ABL1+ cells

Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative disease caused by the constitutive tyrosine kinase (TK) activity of the BCR-ABL fusion protein. However, the phenotype of leukemic stem cells (LSC) is sustained by β catenin rather than by the BCR-ABL TK. β catenin activity in CML is contingent upon its stabilization proceeding from the BCR-ABL-induced phosphorylation at critical residues for interaction with the Adenomatous polyposis coli (APC)/Axin/glycogen synthase kinase 3 (GSK3) destruction complex or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…Accordingly, Cby1 reduced expression in CD34+ cells of CML-CP patients and HP was associated with a significant increment of nuclear beta catenin and enhanced transcription of cyclin D1, a Wnt/beta catenin target gene involved in the maintenance of CD34+ pool (p<0.05 or less) [28]. These findings confirm and expand the results of a recently published study, showing that Cby1-enforced expression is a central component of beta catenin nuclear export and suppression of its transcriptional activity in BCR-ABL1+ cells [29]. In particular, they emphasize Cby1 participation in beta catenin signaling in the LSC compartment responsible for the disease pathogenesis and persistence under TK inhibitor therapy.…”
Section: Resultssupporting
confidence: 88%
“…Accordingly, Cby1 reduced expression in CD34+ cells of CML-CP patients and HP was associated with a significant increment of nuclear beta catenin and enhanced transcription of cyclin D1, a Wnt/beta catenin target gene involved in the maintenance of CD34+ pool (p<0.05 or less) [28]. These findings confirm and expand the results of a recently published study, showing that Cby1-enforced expression is a central component of beta catenin nuclear export and suppression of its transcriptional activity in BCR-ABL1+ cells [29]. In particular, they emphasize Cby1 participation in beta catenin signaling in the LSC compartment responsible for the disease pathogenesis and persistence under TK inhibitor therapy.…”
Section: Resultssupporting
confidence: 88%
“…While nuclear localization sequences have been reported to be present in Cby (Li et al 2010), we did not observe any obvious nuclear accumulation of the Cby-GFP protein, although in cells expressing high levels of the protein, it was found associated with the plasma membrane (not shown). The lack of nuclear localization may be due, at least in part, to the fact that Cby-GFP is thought to cooperate with other proteins to move β-catenin out of the nucleus and into the cytoplasm (Takemaru et al 2003; Li et al 2010; Mancini et al 2013) and perhaps reflects the effects of the expression of the Cby-interacting protein TC1(C8orf4)(Jung et al 2006), whose RNA levels (according to Xenbase) increase following the mid-blastula transition (supplemental figure 4). …”
Section: Resultsmentioning
confidence: 99%
“…Over-expression of Cby has been reported to generate an unfolded protein response in BCR-ABL1 + cells (Mancini et al 2013); whether it has similar effects in other cell types, such as those of the early embryo, is unclear. On the other hand, the absence of Cby could effect β-catenin levels and/or its intracellular distribution, which in turn could influence the activities of other β-catenin-interacting proteins (see (Kormish et al 2010)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cby has been demonstrated to suppress the growth of human colon adenocarcinoma SW480 cells through the inhibition of the canonical Wnt signaling pathway (18). In a recent study, Cby was found to activate endoplasmic reticulum (ER) stress and apoptosis in breakpoint cluster protein/Abl kinase 1-positive human myeloid leukemia cells by inducing the cytoplasmic accumulation of β-catenin (19). Thus, the downregulation of Cby in cancer cells may provide information regarding the use of Cby as therapeutic target and prognostic factor.…”
Section: Introductionmentioning
confidence: 99%